Effect of conjoint use of farmyard manure and fertilizers on yield and nutrient uptake by onion (Allium cepa) and soil fertility - SINGH, HARVENDRA; SINGH, DHARVENDRA; SINGH, SHISHUPAL; PAL, ANIL KUMAR; MUDGAL, S K (The Indian Journal of Agricultural Sciences, 2017)
Field experiment was conducted for two consecutive rabi seasons (2010-11 and 2011-12) at the Research farm, R B S College, Bichpuri, Agra (Uttar Pradesh) to study the effect of conjoint use of FYM and chemical fertilizers on yield and nutrients uptake by onion (Allium cepa L.) and soil fertility. The experiment was laid out in randomized block design with twelve treatments and three replications. The results revealed that the scale leaves/bulb and fresh weight of onion bulb and bulb yields increased significantly up to 150% NPK level over control. The yields of onion bulbs were significantly lower with the sub-optimal dose of NPK fertilizers. All the parameters further increased when 10 tonnes FYM/ha was added along with 100% NPK. An additional bulb yield of 3.35 tonnes/ha was realized with 100 % NPK + 10 tonnes/ha over 100% NPK alone. Application of 100% NPK + 5 kg Zn +1 kg B/ ha produced 32.13 tonnes/ha bulbs and dry matter yield (5.03 tonnes/ha) of onion which was superior to 100 % NPK alone (30.36 and 4.75 tonnes/ha). The maximum protein content (5.75 %) and yield (29.75 q/ha) were obtained with 150% NPK and 100% NPK + 10 tonnes FYM/ha, respectively. The uptake of N, P, K, S, Zn and B by the onion bulbs was found to be associated with production of dry matter resulted by the addition of 100% NPK + 10 t FYM/ha. However, the maximum uptake of Zn (281.0 g/ha) and B (392.1 g/ha) by onion bulbs was noted under 100% NPK+5 kg Zn/ha and 100% NPK + 1 kg B/ha, respectively. The conjoint use of 10 t FYM/ha with 100 % NPK significantly improved the status of available N, P, K, S, Zn and B in post harvest soil over the NPK fertilizers alone. Available B and Zn contents were found to be higher in treatment combination of 100% NPK + 1 kg B /ha and 100 % NPK + 5 kg Zn/ha, respectively. The minimum amounts of available nutrients in post harvest soil were recorded under control treatment.